Development of a Prototype Web-based System for Managing Customer Incoming Letters at PLN ULP Subang using a Design Thinking Approach - Valentina Febrianti; Ahmad Fauzi (Sistemasi: Jurnal Sistem Informasi, 2026)
This study was conducted to design and evaluate a prototype web-based system for managing customer incoming letters in order to improve efficiency and user experience. The method employed is Design Thinking, which includes the stages of empathize, define, ideate, prototype, and testing, with a focus on identifying issues in incoming mail management that still rely on manual processes. The resulting prototype was evaluated using the System Usability Scale (SUS) and the User Experience Questionnaire (UEQ). The results indicate that the system demonstrates a high level of usability, with an average SUS score of 80.6 (categorized as excellent), and provides a positive user experience, as reflected in UEQ scores for attractiveness (1.6), perspicuity (1.7), efficiency (1.5), dependability (1.4), stimulation (1.6), and novelty (1.3). Therefore, the developed system is capable of improving the efficiency of customer incoming letter management while supporting the digitalization of administrative processes and enhancing service quality.